Illegal Self-Emancipation in the Urban Upper South, 1800-1860 - Viola F. Müller (Cahiers du MIMMOC)
Contrary to common assumptions that self-emancipation by flight was only possible to regions outside the southern states, this article argues that many slaves actively took and preserved their freedom by hiding amongst free African American populations in urban areas. In the late eighteenth and early nineteenth centuries, free black communities within the slaveholding southern states emerged or were bolstered as a result of an increase in manumissions. For many African-American slaves, it was an age of emancipation. Yet for most enslaved people living in the US South it was a period of intensification and expansion of human bondage. The developments of the time provided more slaves with new opportunities to escape slavery by fleeing to free black communities.The concept of illegal freedom will be applied, which stands in contrast to the legal freedom that could be obtained on free soil. Few scholars have examined the various strategies employed by self-emancipators to remain concealed from the authorities. This article concentrates on runaway slaves in Baltimore and Richmond, two cities which had large African-American populations. The case will be made that enslaved African Americans carved new spaces of freedom within southern cities, with the assistance of free black communities. It will demonstrate that urban centers within the Upper South were important spaces of illegal freedom for slave refugees, largely because of their numerous free black populations, and that the two group’s experiences were deeply interwoven.